Grafting eco-diasporic identity in Randa Abdel-Fattah’s selected novels - Areej Saad Almutairi,; Ruzy Suliza Hashim,; Raihanah M. M., (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper is based on three selected novels entitled Does My Head Look Big In This? (2005), Ten Things I Hate About Me (2006), and Where The Streets Had A Name (2008) written by Randa Abdel-Fattah (1979), a Palestinian-Egyptian Australian Muslim diasporic writer. In this article, we examine the manifestations of grafting eco-diasporic identity by Abdel-Fattah in order to address how identity graft is operated by interacting with ideology, culture and nature in the contexts of the host land and the homeland as represented in the three selected novels. Using Colin Richards’ theory of graft as a framework, we explore identity contestations of Muslim young adults in the novels from an ecocritical and diasporic perspectives. In the novel Does My Head Look Big In This?, the images of Amal’s sense of being marginalised in the semiosphere of the host land and the sense of self-respect of her Muslim rootedness and heritage of the homeland semiosphere frame the fractured graft of identity. The character of Jamilah, in Ten Things I Hate About Me displays genuine manifestations of the collective emblem of the grafted identity. Finally, the symbol of the iconic jar of the homeland soil and its potentiality of regenerating Hayaat’s identity in Where the Streets Had A Name exhibits the ecological semiosphere in which the grafted identity is shaped. The current discussion, therefore, offers fresh insights into allowing a new horizon for identity grafting in Abdel-Fattah’s works as well as other writers within the tradition of Muslim Diasporic Literature.